How Similarity to Peers and Supervisor Influences Organizational Advancement in Different Cultures - Schaubroeck, John; Lam, Simon S. K. (Academy of Management Journal, 2002)
This study tested hypotheses concerning how similarity of personality traits between promotion candidates and their peers and supervisors influences promotion decisions in different work unit cultures. Personality similarity to peers was positively associated with promotion in units with high individualism. In units with high collectivism, supervisor-subordinate personality similarity was instead a significant predictor of advancement. Behavioral integration between candidates and their peers and supervisors partially mediated the influence of personality similarity on promotion. Demographic similarity had little influence on promotion decisions. We discuss implications for understanding similarity effects and for increasing the validity of promotion decisions.